2020
DOI: 10.1002/jbt.22591
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles and mechanisms of rosmarinic acid in cyclophosphamide‐induced premature ovarian failure

Abstract: The aim of this study was to investigate the protective effect of rosmarinic acid (RA) in a premature ovarian failure (POF) mouse model and the potential mechanisms. The POF model was induced by a single intraperitoneal injection of 120 mg/kg cyclophosphamide (CP). Additionally, 40 mg/kg RA was administered for 7 days before CP injection. The concentration of sex hormones was determined by fluorescence immunohistochemistry. Histological analysis was performed after ovarian tissue sections were stained with hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…This last protein can eventually produce the maturation and release of IL-1β [3]. In previous studies, RA was shown to inhibit inflammasome activation in experimental models of inflammation in epidermal keratinocytes [38], neuroinflammatory injury [39], atherosclerosis [40] and premature ovarian failure [41]. Despite these findings, there is no previous evidence that RA may exert its anti-inflammatory effects through suppression of inflammasome activation in UC.…”
Section: Discussionmentioning
confidence: 99%
“…This last protein can eventually produce the maturation and release of IL-1β [3]. In previous studies, RA was shown to inhibit inflammasome activation in experimental models of inflammation in epidermal keratinocytes [38], neuroinflammatory injury [39], atherosclerosis [40] and premature ovarian failure [41]. Despite these findings, there is no previous evidence that RA may exert its anti-inflammatory effects through suppression of inflammasome activation in UC.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed comparisons were conducted between the control group and the low-dose rapamycin group after 30 days. A single dose of 120 mg/kg CTX was commonly used to establish a mouse model of ovarian dysfunction[ 16 , 17 ]. To determine the underlying mechanism of rapamycin against CTX-mediated ovarian dysfunction, 48 mice were randomly divided into four groups: control group (CC: equal volume saline containing equivalent DMSO), rapamycin treatment group (RC: 5 mg/kg rapamycin for 30 days), CTX-treated group (MC: a single dose of 120 mg/kg CTX at day 24), and rapamycin intervention group (RM: 5 mg/kg rapamycin for 30 days with a single dose of 120 mg/kg CTX at day 24).…”
Section: Methodsmentioning
confidence: 99%
“…With the help of fluorescence immunohistochemistry, histological analysis, Western blot analysis and polymerase chain reaction, RA (40 mg/kg) was investigated to effectively attenuate the abnormal situations of the model including injured ovarian, increased ovarian index, and serum sex hormone levels, the overexpression of the nucleotide-binding oligomerization domain receptor protein-3 (NLRP3) inflammasome, and apoptosis-related proteins in the ovarian. The findings indicate that RA might have a bright prospect in POF treatment in the future [ 274 ].…”
Section: Pharmacologymentioning
confidence: 99%